2016
DOI: 10.18533/jefs.v3i6.204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regional development policies on the resolution of income disparity in China

Abstract: Using thirty provincial panel-data from 1949 to 2010 that is separated into four periods, this paper examines the details of major regional development policies in practice by China so far since its foundation, and focuses on the analysis of how those policies influenced the resolution of inequality between regions through Gini coefficient analysis, coefficient of variation analysis and Theil index analysis. The results of income inequality analysis in Mao's time show that income inequality coefficients are up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Given the number of adverse impacts related to income inequality, a comprehensive study on inequality is justified to formulate policies that can alleviate inequality and ameliorate these adverse effects in the future. Country-specific regional disparity and income decomposition studies have been widely reported for developed (Karakoc, 2017;Kennedy et al, 2017;Kisiała and Suszyńska, 2017;Okabe and Kam, 2017;Bittencourt et al, 2019;Blanco and Ram, 2019) and developing (Choudhury and Chaterjee, 2016;Jang and Jeong, 2016;Paredes et al, 2016;Tian et al, 2016;Habibullah et al, 2017;Sehrawat and Giri, 2018;Calcagnini et al, 2019;Cevik and Correa-Caro, 2019;Le and Nguyen, 2019;Michálek and Výboš tok, 2019;Tchamyou et al, 2019) countries. However, to our knowledge there has been no recent study on the contributions of regional and income subgroups to international inequality for the world.…”
Section: Introductionmentioning
confidence: 99%
“…Given the number of adverse impacts related to income inequality, a comprehensive study on inequality is justified to formulate policies that can alleviate inequality and ameliorate these adverse effects in the future. Country-specific regional disparity and income decomposition studies have been widely reported for developed (Karakoc, 2017;Kennedy et al, 2017;Kisiała and Suszyńska, 2017;Okabe and Kam, 2017;Bittencourt et al, 2019;Blanco and Ram, 2019) and developing (Choudhury and Chaterjee, 2016;Jang and Jeong, 2016;Paredes et al, 2016;Tian et al, 2016;Habibullah et al, 2017;Sehrawat and Giri, 2018;Calcagnini et al, 2019;Cevik and Correa-Caro, 2019;Le and Nguyen, 2019;Michálek and Výboš tok, 2019;Tchamyou et al, 2019) countries. However, to our knowledge there has been no recent study on the contributions of regional and income subgroups to international inequality for the world.…”
Section: Introductionmentioning
confidence: 99%